(untitled) (Educational Knowledge, 2021)
This article addresses the reality of returning migrant children and youth and their integration into the school classroom within the school and community context in areas of high migration flow in Honduras. The objective of the study was to analyze the phenomenon of the return migration experience of children and adolescents in the Honduran context, specifically in the departments of Francisco Morazán, Yoro, Olancho, and Cortés; these departments are representative of the high population convergence with the return migration flow and with participation in school integration processes in Honduras. The research was conducted using a qualitative approach, employing ethnographic elements and document review, and utilizing grounded theory through the techniques of semi-structured interviews and focus groups with a purposive sample of 67 children and adolescents, 31 teachers, and 65 parents and guardians. One of the main findings was that the return and integration of children and adolescents in Honduras does not have a comprehensive integration, therefore, a reconstructive education is required, accessible through curriculum adaptation processes and training for teachers and parents.